2018
DOI: 10.1111/nph.15014
|View full text |Cite
|
Sign up to set email alerts
|

Native soils with their microbiotas elicit a state of alert in tomato plants

Abstract: Several studies have investigated soil microbial biodiversity, but understanding of the mechanisms underlying plant responses to soil microbiota remains in its infancy. Here, we focused on tomato (Solanum lycopersicum), testing the hypothesis that plants grown on native soils display different responses to soil microbiotas. Using transcriptomics, proteomics, and biochemistry, we describe the responses of two tomato genotypes (susceptible or resistant to Fusarium oxysporum f. sp. lycopersici) grown on an artifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 60 publications
7
75
0
Order By: Relevance
“…As in previous studies of plant-microbe interactions, we found that the disruption of rhizosphere microbiomes alters plant performance (Badri et al, 2013;Chialva et al, 2018;Lau & Lennon, 2011) and here specifically defence and several metabolites. As noted above, we found that the differences in the rhizosphere microbiome led to greater differences in defence than did host plant population, and specifically plants grown in the disrupted microbiome treatment experienced significantly higher aphid prevalence (Figure 3b,c) and flea beetle damage (Figure 4).…”
Section: Discussionsupporting
confidence: 82%
“…As in previous studies of plant-microbe interactions, we found that the disruption of rhizosphere microbiomes alters plant performance (Badri et al, 2013;Chialva et al, 2018;Lau & Lennon, 2011) and here specifically defence and several metabolites. As noted above, we found that the differences in the rhizosphere microbiome led to greater differences in defence than did host plant population, and specifically plants grown in the disrupted microbiome treatment experienced significantly higher aphid prevalence (Figure 3b,c) and flea beetle damage (Figure 4).…”
Section: Discussionsupporting
confidence: 82%
“…She also contributes to the collection via two articles (Bonfante, , pp. 982–995; Chialva et al ., , pp. 1296–1308), including a Tansley review which once again mines the fascinating history of mycorrhizal research.…”
Section: Resultsmentioning
confidence: 99%
“…The second hypothesis was surely wrong, but thanks to the collaboration of Thomas Boller in Basel, an outstanding expert in chitinases, and of Pietro Spanu, at that time an undergraduate student in Turin, we performed a detailed study of plant chitinase expression, revealing that it was limited to the early moments of the interaction (Spanu et al ., ). This observation has been largely confirmed by the detection of many chitinases and pathogenesis‐related proteins in transcriptomic studies (Fiorilli et al ., ; Giovannetti et al ., ) and has provided the basis of novel ideas; that is, that the fungus induces priming in the host plant, thus activating a range of molecules related to innate immunity (including chitinases), thereby raising the basal level of defences in the plant (Pozo & AzcĂłn‐Aguilar, ; MartĂ­nez‐Medina et al ., ; Chialva et al ., ).…”
Section: Signalling: a Central Question Of Our Time?mentioning
confidence: 97%
“…This could be a novel trait to be selected when using breeding approaches to generate new crop varieties (Sawers et al, 2008). Lastly, it will be crucial to remember that arbuscular mycorrhizal fungi do not work alone; rather, they belong to a complex microbiota (Chialva et al, 2018). Tailoring the interactions of crop plants and their associated microbiota may provide a crucial advance for sustainable agriculture.…”
Section: The Genetics Underlying Colonization Eventsmentioning
confidence: 99%